Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 15 - Differentiation in Several Variables - 15.1 Functions of Two or More Variables - Exercises - Page 763: 3


$$6,\quad -\frac{1}{6}$$

Work Step by Step

Since $ h(x,y,z)=xyz^{-2}$, then $$ h(3,8,2)=(3)(8)(2)^{-2}=\frac{24}{4}=6$$ $$ h(3,-2,-6)=(3)(-2)(-6)^{-2}=\frac{-6}{36}=-\frac{1}{6}$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.